PEMANFAATAN KEMBALI LIMBAH PADAT LUMPUR PDAM UNTUK PENJERNIHAN AIR DARI SUNGAI MARTAPURA KALIMANTAN SELATAN - Mirwan, Agus (Bumi Lestari; Vol 12 No 1 (2012), 2012)
TThis research aimed to investigate the recovery process of liquid alum derived from sludge solid waste (SSW) Regional Water Company (PDAM) Intan Banjar and the decrease in turbidity and pH of water from Martapura river after the treatmen with recovered liquid alum and other commercial coagulant via coagulation and flocculation. Recovery process was done by dissolving SSW with NaOH and NH4 solution in a flask while stirring and boiling. Then a solution of NH4OH was added to precipitate Al(OH)3 before it was filtered and washed with NH4Cl solution and then it was dried to get dry cake solids. The next process was the reaction between these dry cake solid with H2SO4 to obtain liquid alum. The results showed that liquid alum from SSW-PDAM intan Banjar can be used to reduce turbidity from 43.40 NTU to 7.49 NTU and pH 6.67 to 6.48. While the other commercial coagulants were alum solid coagulant, PAC, FeCl3 and FeSO4 were reduced to 2.11, 1.77, 1.82, and 6.96 for pH respectively. And became to 6.43 NTU, 6.36 NTU, 6.08 NTU, and 28.10 NTU for turbidity respectively.
Keywords: recovery, PDAM sludge, coagulant, water river